2022
DOI: 10.15252/embr.202153191
|View full text |Cite
|
Sign up to set email alerts
|

ZFP207 sustains pluripotency by coordinating OCT4 stability, alternative splicing and RNA export

Abstract: The pluripotent state is not solely governed by the action of the core transcription factors OCT4, SOX2, and NANOG, but also by a series of co-transcriptional and post-transcriptional events, including alternative splicing (AS) and the interaction of RNA-binding proteins (RBPs) with defined subpopulations of RNAs. Zinc Finger Protein 207 (ZFP207) is an essential transcription factor for mammalian embryonic development. Here, we employ multiple functional analyses to characterize its role in mouse embryonic ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(47 citation statements)
references
References 50 publications
6
39
0
Order By: Relevance
“…AS functions in diverse biological processes including cell growth [5], stem cell-renewal and differentiation [6], and cell death [7], to name a few examples. Despite the advantage to expand cellular function, aberrant AS leads to human disease [8].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…AS functions in diverse biological processes including cell growth [5], stem cell-renewal and differentiation [6], and cell death [7], to name a few examples. Despite the advantage to expand cellular function, aberrant AS leads to human disease [8].…”
Section: Introductionmentioning
confidence: 99%
“…N 6 -methyladenosine (m 6 A), the most abundant internal modification in eukaryotic mRNA, has been shown to influence AS [14][15][16][17]. m 6 A is co-transcriptionally deposited by the methyltransferase-like 3 (METTL3) and METTL14 methyltransferase complex, which partially localizes to nuclear speckles, where splicing occurs [18][19][20]. It has been shown that depletion of the Drosophila METTL3 methyltransferase homolog, results in altered AS patterns that influence sex determination [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…AS functions in diverse biological processes including cell growth (6), stem cell-renewal and differentiation (7), and cell death (8), to name a few examples. Despite the advantage to expand cellular function, aberrant AS is typically deleterious to cells and leads to human disease (9).…”
Section: Introductionmentioning
confidence: 99%